The Experiences of American International Students in a Large Irish University - O’Reilly, Aileen; Hickey, Tina; Ryan, Dermot (Journal of International Students, 2015)
Growing numbers of American students are travelling overseas to study abroad and enroll in full degree programs. Despite this trend, relatively little is known about the experiences of United States (U.S.) students abroad. The aim of this research was to examine the experiences of American international students in Ireland. Findings suggest that while U.S. students experience some adaptation problems, overall, they adapt well to studying in Ireland. Subtle differences in long-term and short-term international students’ levels of social support and academic satisfaction were also detected. This research has important practical implications for facilitating the adaption of U.S. students abroad. At a time when many governments and academic institutions are devising strategies to attract international students, this research is timely and necessary.